Interleukin–6 (IL-6) rs1800796 and cyclin dependent kinase inhibitor (CDKN2A/CDKN2B) rs2383207 are associated with ischemic stroke in indigenous West African Men (2017)
Background: Inherited genetic variations offer a possible explanation for the observed peculiarities of stroke in sub - Saharan African populations. Interleukin–6 polymorphisms have been previously associated with ischemic stroke in some non-African populations. Aim: Herein we investigated, for the first time, the association of genetic polymorphisms of IL-6, CDKN2A CDKN2B and other genes with ischemic stroke among indigenous West African participants in the Stroke Investigative Research and Education Network (SIREN) Study. Methods: Twenty-three previously identified single nucleotide polymorphisms (SNPs) in 14 genes of relevance to the neurobiology of ischemic stroke were investigated. Logistic regression models adjusting for known cardio vascular disease risk factors were constructed to assess the associations of the 23 SNPs in rigorously phenotyped cases (N = 429) of ischemic stroke (Men = 198; Women = 231) and stroke– free (N = 483) controls (Men = 236; Women = 247). Results: Interleukin-6 (IL6) rs1800796 (C minor allele; frequency: West Africans = 8.6%) was significantly associated with ischemic stroke in men (OR = 2.006, 95% CI = [1.065, 3.777], p = 0.031) with hypertension in the model but not in women. In addition, rs2383207 in CDKN2A/CDKN2B (minor allele A with frequency: West Africans = 1.7%) was also associated with ischemic stroke in men (OR = 2.550, 95% CI = [1.027, 6.331], p = 0.044) with primary covariates in the model, but not in women. Polymorphisms in other genes did not show significant association with ischemic stroke.